1976
DOI: 10.1113/jphysiol.1976.sp011360
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of cellular volume in renal cortical slices incubated in hyposmotic medium.

Abstract: SUMMARY1. Changes in water and ion contents of renal cortical slices from rat, rabbit and guinea-pig incubated in medium of a half normal osmolarity were followed over 60 min incubation at 25°C.2. Metabolizing slices gained water and lost sodium and chloride but not potassium. These changes reflected in part changes in cellular composition, and were complete within 5 min. A new steady-state was then maintained for a further 55 min.3. Slices initially incubated for 60 min with ouabain, also lost sodium and chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…These results are similar to those obtained by Kregenow (1971a) in duck erythrocytes, who also showed a significant drop in red cell K concentration. Hughes and MacKnight (1976) showed no change in cell K content at 25°, but, on recalculating their data, we found that a drop in cell concentration of K was also evident. The differences between theirs and the present experiments may be due to the different temperatures and the presence of bicarbonate in ours.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…These results are similar to those obtained by Kregenow (1971a) in duck erythrocytes, who also showed a significant drop in red cell K concentration. Hughes and MacKnight (1976) showed no change in cell K content at 25°, but, on recalculating their data, we found that a drop in cell concentration of K was also evident. The differences between theirs and the present experiments may be due to the different temperatures and the presence of bicarbonate in ours.…”
Section: Discussionmentioning
confidence: 89%
“…In hypotonic solutions, renal tubular cells swell and then, in time, return incompletely to their original volume (Dellasega and Grantham, 1973;Hughes and MacKnight, 1976;Gyory, Kweifio-Okai and Ng, 1981). This tendency to restore original cell volume is referred to as volume regulation and is incomplete in renal epithelial cells but nearly complete in red cells (Kregenow, 1971a;Schmidt and McManus, 1977).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations